KESANTUNAN SEMU PADA TINDAK TUTUR EKSPRESIF MARAH DALAM BAHASA INDONESIA - Ekawati, Mursia (Sunan Kalijaga State Islamic University Yogyakarta, 2017)
Verbal anger is an expressive speech act. The language function that supported by expressive speech act is interactional, which is used to reveal social relationship and private attitude. The aims of this research is to get patterns of verbal anger in terms of expressive speech act in Bahasa. This research uses socio-pragmatic method to analyze through speech components, involving sociolinguistics and implicature. Data analysis is done by explaining the marker shapes as the indicator of anger and to whom (P1, P2 or P3) the anger is for. The result shows that speech act of anger are done through indirect sentences (interogative and affirmative sentences), implicit meanings and focus on the third party (P3). Anger to third party is realised as a pseudo politeness. The function of pseudo politeness is also for maintaining the social relationship between friends, families, and communities. This speech act of anger can be done through indirect sentences with the explicit meaning and focus on second party (P2). It is also done through direct sentences and explicit meanings with or without response from P2.